Adult Attachment for Reconstructing Adolescents’ Learning Identity and Awareness - Dewi, Ratna Sari; Nurhayati, Nurhayati (Sukma: Jurnal Pendidikan, 2019)
This study explored how adolescents reconstructed their roles as learners through learning identity and awareness by adult involvement in Sukma Bangsa Pidie (SBP) School. In order to monitor students’ attitudes and learning aspects’ progress, this research employed several observations and interviews (groups and individuals) either by videotaping or voice recording, also students’ database records from school information system (called SISTO). The previous findings advocated that there were variations in the way adolescents performed their learning identity that might encourage them to achieve different degrees of motivation, self-perceptions (self-efficacy, self-concept, and self-esteem), autonomy, and self-development towards their identity as learners. In the other study, the authors also found that students in SBP School were in various categories regarding their levels of learning awareness. It was exhibited by how students dealt with their own learning approaches and how high their existing willingness to learn was. The different levels of learning awareness were survival, establishing stability, approval, and loving to learn. Both learner identity and learner awareness level were almost similar in the way that adolescents experienced. As argued by previous well-known researchers, the child would grow as a good learner with positive improvement of self-concept and self-esteem. Also, the formation of positive self-esteem in adolescence became a bridge towards their success as demanding learners. Furthermore, adult (in this case teachers and parents) involvement with adolescents’ learning approaches may embolden the learners to become less or more autonomous people. Positive adult attachment therefore is pivotal to moderate students who have either low willingness to study or low self-conception. This study ultimately confirmed that there was a reciprocal relationship between learner identity (motivation, self-perceptions, autonomy, self-development) and learner awareness (survival, establishing stability, approval, loving to learn), then further will support the integrated effects on learner autonomy.